2021
DOI: 10.3390/electronics10222846
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Collaborative Work in the COVID-19 Era: Use of Breakout Groups in Teaching L2 Translation

Abstract: Social distancing became a must during the pandemic, which not only had implications for people’s social lives, but also for their learning. Collaborative work was almost impossible, especially in the classroom, despite a great need for this approach. For example, in their translation classes, the learners needed to collaborate with their peers, assisting each other in translating texts. Thus, the use of breakout groups is proposed in this study, although there is no guarantee that learners will accept this on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…In addition, they share solutions to any problems they face on their worksheets. This is in line with the results of the studies by Oraif and Elyas [63], and Metscher et al [64], who emphasize the privacy that breakout groups enjoy, which gives psychological comfort to students when they interact.…”
Section: Plos Onesupporting
confidence: 89%
“…In addition, they share solutions to any problems they face on their worksheets. This is in line with the results of the studies by Oraif and Elyas [63], and Metscher et al [64], who emphasize the privacy that breakout groups enjoy, which gives psychological comfort to students when they interact.…”
Section: Plos Onesupporting
confidence: 89%
“…Previous research (Alwazna, 2021; Cortez and Schrijver, 2021; Khoury et al. , 2021; Oraif and Elyas, 2021; Su et al. , 2021) has indicated that teaching and learning translation remotely can fulfill the instructional and educational objectives effectively, as online platforms help teachers provide students with numerous online resources and motivating activities.…”
Section: Methodsmentioning
confidence: 99%
“…To address this problem, previous research (Chan, 2014;Kim, 2019;Su et al, 2021) examined online translation classes to shed light on blended learning rather than full online learning classes. Moreover, previous research SJLS 3,3 (Alwazna, 2021;Cortez and Schrijver, 2021;Khoury et al, 2021;Oraif and Elyas, 2021;Su et al, 2021) has concluded that teaching and learning translation remotely can fulfill the instructional and educational objectives effectively. However, Almahasees and Qassem (2021) argued that online translation education and learning cannot replace face-to-face instruction, therefore blended learning is the most effective approach.…”
Section: Online Distance Learning Translation Classes During the Covi...mentioning
confidence: 98%
See 1 more Smart Citation
“…The breakout of COVID-19 is seen as the worst catastrophe globally since the World Wars. COVID-19 has infected 213 nations and territories with (confirmed) sick patients, and the total is growing steadily [6,7]. The COVID-19 pandemic was associated with a stressful effect.…”
Section: Introductionmentioning
confidence: 99%